The kinematic history of the Khlong Marui and Ranong Faults, southern Thailand - Watkinson, I.; Elders, Chris; Hall, R. (Pergamon-Elsevier Science Ltd., 2008)
The Khlong Marui Fault (KMF) and Ranong Fault (RF) are major NNE-trending strike-slip faults which dissect peninsular Thailand. They have been assumed to be conjugate to the NW-trending Three Pagodas Fault (TPF) and Mae Ping Fault (MPF) in Northern Thailand, which experienced a diachronous reversal in shear sense during India–Eurasia collision. It follows that the KMF and RF are expected to show the opposite shear sense and a slip sense reversal at a similar time to the TPF and MPF. New field data from the KMF and RF reveal two phases of ductile dextral shear separated by Campanian magmatism. Paleocene to Eocene post-kinematic granites date the end of this phase, while a brittle sinistral phase deforms the granites, and has exhumed the ductile fault rocks. The timing of these movements precludes formation of the faults in response to Himalayan extrusion tectonics. Instead, they formed near the southern margin of a Late Cretaceous–Paleocene orogen, and may have been influenced by variations in the rate of subduction ahead of India and Australia. North-south compression prior to reactivation of the subduction zone around southern Sundaland in the Eocene caused widespread deformation in the overriding plate, including sinistral transpression on the KMF and RF.